ISDC Review of 2025-2030 Research and Innovation Inception Reports - CGIAR Independent Science for Development Council (CGIAR Independent Advisory and Evaluation Service, 2025)
The Independent Science for Development Council (ISDC) reviewed CGIAR’s Inception Reports for the 2025–2030 Science and Innovation Portfolio to assess whether the research environment is adequately equipped to support high-quality science and achieve meaningful global impact. Commissioned by the CGIAR System Council, the review aimed to verify that gaps identified in late 2024 were effectively addressed by mid-2025.